Relational Database Model Design to Support School Library Digitalization in Bekasi City Using Database Life Cycle - Vion Age Tricahyo; Linda Ika Mayasari; Laylatul Munawaroh; Wisnu Putri Airmas Jati; Adam Surya Handika; Indra Ramadani Ridwan (LKP KARYA PRIMA KURSUS, 2026)
The digital transformation of school libraries in Bekasi City has become increasingly imperative to overcome the limitations of fragmented and non-integrated manual management systems currently implemented across educational institutions. Such conditions hinder efficient collection management, circulation monitoring, data reporting, and evidence-based decision-making, all of which are essential components in supporting school literacy programs. Library digitalization represents a strategic initiative to transform conventional library services into technology-enabled learning ecosystems. Through the integration of digital technologies, libraries can effectively manage both physical and electronic collections, provide seamless access to information resources, and foster students’ digital literacy competencies in alignment with the demands of contemporary education. This study aims to develop a centralized and standardized relational database model capable of supporting integrated digital library operations across schools in Bekasi City. To achieve this objective, the Database Life Cycle (DBLC) methodology was adopted as the primary framework for database development. The research process comprised four sequential phases: (1) requirements analysis, (2) Entity Relationship Diagram (ERD) design and database normalization, (3) physical database implementation using a Database Management System (DBMS), and (4) functional testing and validation of the database. By employing this systematic approach, the study produces a robust, scalable, and maintainable database blueprint that can serve as the foundational infrastructure for the development of an integrated digital school library platform in Bekasi City.